Phosphate Fertilizer on Growth Response Time of Soybean Varieties Under Rubber Plant - Muhammad Rizwan; Indra Gunawan; Fitra Syawal Harahap (Agrosains : Jurnal Penelitian Agronomi, 2024)
Research which aims to determine the response of several varieties of soybean plants to the time of application of phosphate fertilizer under stands of rubber plants has been carried out at the Sungai Putih Research Institute, Galang District, Deli Serdang Regency, North Sumatra Province. The method used was a Factorial Randomized Block Design method with two factors. The first factor was several soybean plant varieties (Anjasmoro, Dega 1, Dena 1, and Devon 2). The second factor was the time of administration of the phosphate fertilizer dose (111 g/plot giving phosphate fertilizer 1 week before planting, 111 g/plot giving phosphate fertilizer at planting time, and 111 g/plot giving phosphate fertilizer 1 week after planting). The parameters observed were plant height, amount of leaf chlorophyll, flowering time, number of filled pods, number of empty pods, seed weight and weight of 100 seeds. The research results showed that the treatment of several varieties had a significant effect on all observation parameters. The timing of phosphate fertilizer application had a significant effect on plant height, flowering age, number of filled pods, seed weight and 100 seed weight, but had no significant effect on the amount of leaf chlorophyll and the number of empty pods. The interaction between the two treatments had no significant effect.